2007
DOI: 10.1126/science.1136221
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale Eddies Drive Increased Silica Export in the Subtropical Pacific Ocean

Abstract: Mesoscale eddies may play a critical role in ocean biogeochemistry by increasing nutrient supply, primary production, and efficiency of the biological pump, that is, the ratio of carbon export to primary production in otherwise nutrient-deficient waters. We examined a diatom bloom within a cold-core cyclonic eddy off Hawaii. Eddy primary production, community biomass, and size composition were markedly enhanced but had little effect on the carbon export ratio. Instead, the system functioned as a selective sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
232
8
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 268 publications
(258 citation statements)
references
References 23 publications
17
232
8
1
Order By: Relevance
“…In general, pre and post each trap deployment, a larger scale CTD survey grid was sampled. Diatom biomass was estimated using a fucoxanthin algorithm (μg diatom C l -1 = 0.288 * ng fucoxanthin l -1 -0.012; R 2 = 0.713 and n = 130) derived from pigment and biovolume measurements during E-Flux III (Benitez- Nelson et al, 2007) and from outside the iron-fertilized patch in SOFeX (Coale et al, 2004) where similar diatom assemblages were observed. The biomass of non-diatom photosynthetic picoeukaryotes ("Peuks") and Synechococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…In general, pre and post each trap deployment, a larger scale CTD survey grid was sampled. Diatom biomass was estimated using a fucoxanthin algorithm (μg diatom C l -1 = 0.288 * ng fucoxanthin l -1 -0.012; R 2 = 0.713 and n = 130) derived from pigment and biovolume measurements during E-Flux III (Benitez- Nelson et al, 2007) and from outside the iron-fertilized patch in SOFeX (Coale et al, 2004) where similar diatom assemblages were observed. The biomass of non-diatom photosynthetic picoeukaryotes ("Peuks") and Synechococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Eddies are pervasive and long-lived turbulent swirls in the ocean on scales of 10 to a few 100 km (Rhines 2001). These mesoscale features of the ocean are hotspots of biogeochemical and biological activity (Weimerskirch et al 2004, Benitez-Nelson et al 2007). Various mechanisms explain how eddies can fuel biological production in open-ocean ecosystems, leading to patches of enhanced productivity in zones of low primary production.…”
Section: Introductionmentioning
confidence: 99%
“…Various mechanisms explain how eddies can fuel biological production in open-ocean ecosystems, leading to patches of enhanced productivity in zones of low primary production. Cyclonic eddies can generate upwelling of deepcold-nutrient-rich waters towards upper euphotic surface layers in their centre (McGillicuddy et al 1998, Bakun 2006, enhancing local primary production (Seki et al 2001, Mizobata et al 2002, Benitez-Nelson et al 2007). Anticyclonic eddies can also generate an upward movement of rich waters, but located around their edge, where phytoplankton enrichment has also been observed (Mizobata et al 2002, Quartly & Srokosz 2004.…”
Section: Introductionmentioning
confidence: 99%
“…This allows a particular group of organisms to thrive, as the submesoscale patches are stable on the same time scale (days to weeks) as phytoplankton bloom development, but this same landscape will ultimately destroy these patches through mixing, resulting in competition and succession of the newly mixed phytoplankton functional types. Within this paradigm, the authors argue that previously well-studied examples of physicalbiological systems with defined phytoplankton communities, such as mesoscale eddies (15), are simply a special case of the more general phenomenon described in this contribution.…”
mentioning
confidence: 99%